Increase in fruit and seed size, and seeds per fruit in allspice (Pimenta dioica L. Merr.) by hormonal application - REMA, B KRISHNAMOORTHY, K S KRISHNAMURTHY, J (Journal of Spices and Aromatic Crops, 1995)
Allspice (Pimenta dioica L. Merr.) is indigenous to West Indies and tropical America and the spice of commerce is the dried fully mature unripe fruits. Jamaica is a major producer of allspice in the world. In India, the crop is grown in parts of Kerala, Tamil Nadu and Maharashtra. At the Experimental Farm of Indian Institute of Spices Research (IISR), Peruvannamuzhi (Kerala State, India), 135 lines of allspice are being maintained in the germplasm.